Rapid and Routine Molecular Typing Using Multiplex Polymerase Chain Reaction and MinION Sequencer - Liao, Yu-Chieh; Wu, Han-Chieh; Liou, Ci-Hong; Lauderdale, Tsai-Ling Yang; Huang, I-Wen; Lai, Jui-Fen; Chen, Feng-Jui (Frontiers in Microbiology, 2022)
Molecular typing is an essential tool that has been extensively applied in laboratories as well as in clinical settings. Next-generation sequencing technologies promise high-throughput and cost-effective molecular applications; however, the accessibility of these technologies is limited due to the high capital cost. Oxford Nanopore Technologies (ONT) offers a MinION device with the advantages of real-time data analysis, rapid library preparation, and low cost per test. However, the advantages of the MinION device are often overshadowed by its lower raw accuracy. Herein, we present a concise multilocus sequence typing protocol of Staphylococcus aureus using multiplex polymerase chain reaction and Rapid Barcoding Kit for barcoding and MinION device for sequencing. Moreover, to clarify the effects of carryover DNA on tasks that require high sequence accuracy, we used the MinION flow cell in successive runs of washing and reusing. Our results revealed that the MinION flow cell could achieve accurate typing of a total of 467 samples with 3269 kilobase-long genes within a total of 5 runs. This thus demonstrates the effectiveness of a portable nanopore MinION sequencer in providing accurate, rapid, and routine molecular typing.